CSR (CORPORATE SOCIAL RESPONSIBILITY ) : A DIALOGUE TO THE STAKEHOLDERS AND ITS VALUE TO ECONOMIC GROWTH AND SUSTAINABILITY IN INDONESIA - Yeni Rosilawati, MM, Adhianty Nurjanah,M.Si (2012)
Corporate social responsibility (CSR) is a strategic corporate initiative that has been receiving an increased amount of attention internationally. It provides more benefits to an organisation than simply reducing costs by environmental measures such as recycling and giving back to the community. Corporate social responsibility is intended to encourage the business’ world to be more ethical in their activities so they have no influence or a negative impact on society and the environment, so that eventually the business will be able to survive on an ongoing basis to obtain the economic benefits which it has been the establishment of the business world. According to Sriramesh et al (2007:1) CSR is needed by a corporate to go beyond their economic and legal obligations, and act responsibly towards multiple stakeholders including societies. We have seen that many high profile corporations in the world have failed to gain public confidence and are considered not trustworthy because of their dishonourable conduct. The cases show how important is the role of open the business with more responsibility towards stakeholders. The corporate Social Responsibility (CSR) is a hot topic among the companies, representatives of academia and NGO but also among the specialists that coming from a wide range of national and international administrative institutions. In Indonesia, CSR had been implemented by various companies ranging from a wide array of small, medium, local, national and global company. Good management of CSR is needed and will cause a benefit for the company and the stakeholders. CSR is needed by a corporate to go beyond their economic and legal obligations, and act responsibly towards multiple stakeholders including societies. By better understanding of CSR among practioners in Indonesia , therefore it enhance designing a good CSR strategy